2020
DOI: 10.1007/s10620-020-06328-w
|View full text |Cite
|
Sign up to set email alerts
|

To Protect Fatty Livers from Ischemia Reperfusion Injury: Role of Ischemic Postconditioning

Abstract: Background The benefit of ischemic postconditioning (IPostC) might be the throttled inflow following cold ischemia. The current study investigated advantage and mechanisms of IPostC in healthy and fatty rat livers. Methods Male SD rats received a high-fat diet to induce fatty livers. Isolated liver perfusion was performed after 24 h ischemia at 4 °C as well as in vivo experiments after 90 min warm ischemia. The so-called follow-up perfusions served to investigate the hypothesis that medium from IPostC experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies show that IPOC is able to reduce IR injuries in a variety of tissues including the lung, 14 kidney, 15 heart, 16 intestine, 17 brain, 18 and liver. 19 Goodman et al have shown that the protective effects of post-conditioning against IR injuries are mediated via activation of the JAK-STAT pathways in the isolated mouse heart. 20 However, there is not enough evidence to show the possible role of the JAK-STAT signaling pathway in the protective effects of IPOC against the hepatic injury induced by IR.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that IPOC is able to reduce IR injuries in a variety of tissues including the lung, 14 kidney, 15 heart, 16 intestine, 17 brain, 18 and liver. 19 Goodman et al have shown that the protective effects of post-conditioning against IR injuries are mediated via activation of the JAK-STAT pathways in the isolated mouse heart. 20 However, there is not enough evidence to show the possible role of the JAK-STAT signaling pathway in the protective effects of IPOC against the hepatic injury induced by IR.…”
Section: Introductionmentioning
confidence: 99%